An Efficient Dual‐Mode Solar Spectral Modification for c‐Si Solar Cells in Tm3+/Yb3+ Codoped Tellurite Glasses. Issue 7 (8th April 2016) - Zhou, Xianju; Shen, Jun; Wang, Yongjie; Feng, Zhongshan; Wang, Rongxue; Li, Li; Jiang, Sha; Luo, Xiaobing
Abstract : A series of Tm 3+ /Yb 3+ codoped tellurite glasses, which demonstrate an interesting dual‐mode solar spectral converting for c‐Si solar cells, have been successfully prepared by conventional high‐temperature melt‐quenching technique. The photoluminescence (PL), photoluminescence excitation (PLE) spectra along with the decay curves have been studied systematically. The results indicate that the transparent glasses show two distinguishable near infrared (NIR) spectral converting behaviors, that is, quantum cutting (QC) and downshifting (DS) processes, sensitized by narrow f–f transition absorption of Tm 3+ : 3 H6 → 1 G4 at 465 nm and broad absorption band due to charge‐transfer state (CTS) of Yb 3+ ‐O 2− at 320 nm, respectively. The Tm 3+ /Yb 3+ codoped tellurite glasses convert ultraviolet (240–400 nm) and blue (450–490 nm) photons into NIR (920–1100 nm) ones, which well match the optimal spectral response of silicon (Si) solar cells. The prepared tellurite glass can be potentially utilized as spectral converter to improve the photovoltaic conversion of c‐Si solar cells. The dual‐mode solar spectrum converting material might explore a novel approach to realize UV‐Vis to NIR downconversion for Si solar cells application.